Thermodynamic inconsistency disproves the Suga-Sagawa theory of cardiac energetics. (September 2021) - Loiselle, Denis S.; Taberner, Andrew J.; Tran, Kenneth; Han, June-Chiew
Abstract: The theory proposed by Suga and Sagawa, encompassing the concepts of 'time-varying elastance', 'pressure-volume area' and 'isoefficiency', has been widely applied in cardiac research - albeit not without contention. In this Review, we commence with a brief history of striated muscle energetics as a prelude to re-visiting the Suga-Sagawa Theory. We conclude our discussion by including recent insights into the fundamental flaw underlying the metabolic component of the Theory.